(untitled) (Jurnal Sejarah Indonesia, 2025)
G. R. Knight’s article entitled "Peasant Labor and Capitalist Production in Late Colonial Indonesia: The ’Campaign’ at a North Java Sugar Factory, 1840-1870" is very interesting. However, if viewed from the title, the spatial aspect of this article is very broad, namely northern Java. This does not match what Knight explained in the content section which only took a case study in Wonopringgo, one of the areas in Pekalongan. If so, Knight should have immediately said the Wonopringgo or Pekalongan area. However, if using the terminology of North Java, in the author’s opinion, using more than one case study. This is because what happened in Wonopringgo cannot then be equated with what happened in eastern or western North Java. So it would be more interesting if this article used a comparison with eastern and western North Java, for example what happened in Pasuruan and Cirebon. The author uses the theory of structuralism to see an event in society as a whole. This theory makes an event have a reciprocal relationship between parts and between parts and the whole.